METAFORA VISUAL PADA IKLAN OBAT ANTISEPTIK VIDISEP KAJIAN SEMIOTIKA - Riki Himawan Mulyadi; Agung Eko Budiwaspada (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2021)
One of the ways commonly used to increase the appeal of an advertisement is to use a visual rhetorical approach. Vidisep's antiseptic drug advertisement is an advertisement that uses a visual rhetorical approach. Vidisep's ad won the highest award in the print media advertising category in Citra Pariwara in 2016. This indicates that as a visual work, this ad is considered to have met the requirements in terms of creativity in its visualization. However, it is not known how the correlation between creative advertising and the response from consumers. This research aims to determine the response of consumers to advertisements that use a visual rhetorical approach. The method used in this research is a qualitative method. Data collection was carried out through in-depth interviews. In the early stages, research was carried out aimed at identifying the types of visual rhetoric in Vidisep's advertisements. Meanwhile, the second stage is the main research, namely consumer response alertness to advertisements. The results of the analysis in the first phase of research showed that Vidisep's advertisement used a trope-type rhetorical figurative mode, with destabilization operations. Meanwhile, the results of the second phase of research show consumer responses related to attitudes towards recommending that the manufacturer's reputation can reduce doubts about product quality. Attitude toward the advertisement and its execution can only provide entertainment. The meaning that occurs does not do much to overcome doubts on the brand.